Temporal evolution of fibroblast responses following salivary gland ductal ligation injury - Tavarez, Joey R.; Kenney, James; Gabunia, Sergo; Nelson, Deirdre A.; Larsen, Melinda (Frontiers in Dental Medicine, 2025)
Extracellular matrix remodeling is a natural response to injury but, excessive extracellular matrix accumulation, or fibrosis, is a causative factor in hundreds of diseases that limit organ function, regenerative responses, and can interfere with regenerative therapies. Fibrosis is closely related to inflammation, both of which occur in the salivary glands of patients treated with radiation for head and neck cancers and in patients suffering from autoimmune conditions, such as Sjögren's Disease. Despite the known involvement of fibrosis in disease and the inhibitory effects of fibrosis on tissue regeneration, the mechanisms through which extracellular matrix is elaborated in the salivary gland are poorly understood. Stromal fibroblasts are the primary matrix-producing cells and are known to drive both fibrosis and inflammation. To define the temporal responses of fibroblasts to injury, we induced a temporary obstructive injury though ligation of the primary submandibular and sublingual salivary gland ducts and then performed single-cell RNA sequencing and pathway analysis at timepoints immediately following the injury. Using bioinformatic approaches, we identified three unique fibroblast groups that dynamically respond to the injury. We characterized the changes in matrisomal and inflammatory gene expression over a 7-day time course and identified one group of fibroblasts to be the primary injury-responsive fibrogenic cell type. Understanding how fibroblasts respond at the early and later injury timepoints, along with defining signaling pathways regulated by fibroblasts, could lead to a better understanding of the contribution of fibroblast to acute injury responses to facilitate the development of therapeutics that minimize fibrosis and promote regenerative gland responses in chronic disease states.